Protean Form in Washington Square: Linguistic Experimentation and the Anticipation of Life. Issue 2 (2nd July 2016) - Williams, Merle
Abstract : Although Washington Square appears to be a thoroughly assured and compactly structured novel bearing testimony to Henry James's predilection for dramatic representation, the text provides a site for fertile experimentation with the protean possibilities of fictional form. Washington Square is a realist novel that is not quite realist. While James pays close attention to such pertinent factors as time, place, characterisation and dialogue, a fleeting autobiographical interpolation begins to destabilise predictable generic assumptions. As the narrative unfolds, the reader is drawn into engaging with aspects of the plot that suggest both a moving drama of intense psychological struggle and a modern domestic tragedy. At the same time, the text calls into question frequently accepted referential links to the experiential world by subtly foregrounding its affiliations to the processes of aesthetic production. From this perspective, the protean potential of Washington Square may be regarded as more closely related to Jane Austen's Northanger Abbey, Honoré de Balzac's Eugénie Grandet or Victor Cherbuliez's now obscure Le Comte Kostia (1863) than to conventionally acknowledged mimetic principles. Such an interpretation is reinforced by James's consistent foregrounding of the flexible linguistic play of his narrative. Irony is the dominant modality of both the narrator and Dr Sloper, while melodrama in quite distinct guises becomes the expressive medium of the Doctor, as well as his foolishly interfering sister, Mrs Penniman. Morris Townsend, as disingenuous suitor, is an accomplished manipulator of language. This leaves Catherine, the disappointing daughter, vulnerable heiress and rejected bride, to complete the dynamic equilibrium of a rhetorical square (reflecting the title of the novel) with the pathos of her silent endurance. Yet Catherine's quiet inwardness serves equally as the ethical focus of James's story. Her frustrated anticipation of, and yearning for, a life of modest recognition and emotional reciprocity is poised against the glittering repartee of James's scenes and the imaginative cleverness required by the aesthetic enterprise. It is ultimately Catherine's consciousness that consumes the verbal gymnastics of the novel into the privacy of her chastened, yet resilient, existence. As James understands, the rest must be silence.